1985
DOI: 10.1002/aja.1001740304
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate determinants involved in mammalian fertilization

Abstract: During fertilization in mammals, the male and female gametes undergo a form of highly complex cell-cell recognition whereby a nonspecific initial binding is followed by a species-specific penetration of the zona pellucida. Recent data from many species have demonstrated the involvement of surface carbohydrates in regulating fertilization at both these stages. The potential benefits as well as drawbacks of three major techniques used so far are discussed, and the need for a cautious interpretation of the data i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
35
0

Year Published

1987
1987
1998
1998

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(39 citation statements)
references
References 68 publications
(64 reference statements)
4
35
0
Order By: Relevance
“…Accordingly, the inhibitory saccharides could block sperm-egg adhesion by competitively blocking the sperm adhesion sites on the zona pellucida. Similar results have been obtained in mouse, rat, and guinea pig spermatozoa [see Ahuja, 1985a, for a review].…”
Section: Zona-binding Sites On the Sperm Surfacesupporting
confidence: 73%
“…Accordingly, the inhibitory saccharides could block sperm-egg adhesion by competitively blocking the sperm adhesion sites on the zona pellucida. Similar results have been obtained in mouse, rat, and guinea pig spermatozoa [see Ahuja, 1985a, for a review].…”
Section: Zona-binding Sites On the Sperm Surfacesupporting
confidence: 73%
“…The chemical nature of these complementary recognition sites is poorly understood, although there is growing evidence that carbohydrate moieties on surface membrane glycoconjugates are involved in these interactions (1,34).…”
mentioning
confidence: 99%
“…Specific carbohydrate upon hydration. Thus modifications of the anuran egg extracelmoieties mediate sperm-zona pellucida interaction in mice [2], lular matrix are fundamental processes that regulate sperm-egg hamsters [3], and rats [4]. Alves et al [5] have shown that sul-interaction in fertilization.…”
mentioning
confidence: 99%